2019
DOI: 10.1007/s00221-019-05627-7
|View full text |Cite
|
Sign up to set email alerts
|

Associations between genetic variations and global motion perception

Abstract: The cholinergic system is known to strongly modulate perceptual and cognitive processes, and the alpha7 subunit of the cholinergic nicotinic receptor (CHRNA7) is broadly expressed within the visual system. Here, we assessed whether genetic variations of the alpha7 subunit of the cholinergic nicotinic receptor gene (CHRNA7) affect coherent motion perception. Motion perception has been shown to decline with age, and it has previously been suggested that effects of genetic variations are magnified by age. Therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
1
1
0
Order By: Relevance
“…Our findings suggest that the performance increase due to cholinergic activation is specific to certain stimulus parameters (i.e., contrast) and age groups. Although these findings are in agreement with the behavioral studies on humans reporting that cholinergic transmission plays an important role in motion processing (e.g., Kunchulia et al, 2019), they also emphasize that there is a complex relationship between visual stimulation and cholinergic system during neural aging. In fact, previous studies on the primary visual cortex showed the ACh level significantly increases response gain in the contrast domain.…”
Section: Age and Genotype Interaction In The Contrast Domainsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings suggest that the performance increase due to cholinergic activation is specific to certain stimulus parameters (i.e., contrast) and age groups. Although these findings are in agreement with the behavioral studies on humans reporting that cholinergic transmission plays an important role in motion processing (e.g., Kunchulia et al, 2019), they also emphasize that there is a complex relationship between visual stimulation and cholinergic system during neural aging. In fact, previous studies on the primary visual cortex showed the ACh level significantly increases response gain in the contrast domain.…”
Section: Age and Genotype Interaction In The Contrast Domainsupporting
confidence: 92%
“…Surprisingly, despite the evidence demonstrating the various contributions of the cholinergic system to visual processes, its specific roles in age-related changes in visual motion perception have not been studied extensively. Using genetic variations in the alpha 7 subunits of cholinergic nicotinic receptor (CHRNA7), a recent study investigated the relationship between the cholinergic system in humans and agerelated changes in motion perception (Kunchulia et al, 2019). The behavioral findings suggest that genetic variations are associated with perceptual performance on direction discrimination, but these associations seem to be unrelated to age-related changes.…”
Section: Introductionmentioning
confidence: 99%